Integrating Digital Technologies for Sustainable Tourism: Quantitative Assessment of Tech-Enabled Organizational Practices - Supiah Ningsih; Rudy Irwansyah; Danil Syahputra; Inda Arfa Syera; Muhammad Arief Tirtana (Advance Sustainable Science Engineering and Technology, 2026)
This study examines how digital transformation technologies drive sustainability performance in the tourism sector by integrating Internet of Things (IoT), artificial intelligence (AI), and big data analytics into organizational culture and leadership. A mixed dataset of 300 tourism enterprises in Asahan Regency, Indonesia, complemented by technical indicators such as energy consumption (kWh) and IoT penetration, was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Tech-Enabled Organizational Culture (TE-OC) (β = 0.487, p < 0.001) and Tech-Enabled Green Leadership (TE-GL) (β = 0.531, p < 0.001) significantly influence Smart Green Culture (SGC), which has the strongest effect on Technology-Supported Sustainable Tourism Performance (TS-STP) (β = 0.664, p < 0.001; R² = 0.651). While the direct effects of TE-OC and TE-GL on TS-STP are limited, their indirect effects through SGC are substantial, indicating that digitally enabled culture plays a key mediating role. The findings suggest that competitiveness in sustainable tourism depends not only on managerial orientation but also on measurable investments in digital technologies. Limitations include the cross-sectional design and reliance on self-reported data; future research should incorporate longitudinal sensor-based data and comparative analyses across destinations.